Rethinking the Brazilian transport sector: historical lessons learned and support paths for the energy transition. - Zacharias, Luis Guilherme Larizzatti (2022)
The transport sector is Brazil\'s largest energy consumer and is responsible for a large part of Brazil\'s greenhouse gas emissions and air pollution. Therefore, Brazil must establish strategies and pathways for a low-carbon transition. In this context, the central aim of this research is to contribute with a historical analysis of the transport and fuel system in the face of the problems addressed above, seeking to understand how the dynamics of fuel transitions occurred in the history of Brazil. The first covers a historical approach to the events and facts that marked the evolution of transport in Brazil. The second covers a technical-economic analysis of the evolution of natural gas vehicle technology in two Brazilian states. Both perspectives are based on three essential aspects for the prosperity of an energy transition: technology, domestic fuel, and infrastructure. This research seeks to answer the following general research question: \"What can we learn from the history of the Brazilian transport sector, rethinking new paths for a low carbon energy transition?\" This work is divided into two articles. The first article seeks to review the history of the Brazilian transport sector, identifying the events that marked the evolution of the sector within the fields of technology, domestic fuel, and infrastructure. The second article aims to analyze the adoption and development of vehicles powered by natural gas at the state level (Rio de Janeiro and São Paulo) through seven performance parameters for vehicle adoption. As a result of the first paper, some lessons can be learned: (i) the formation of the Brazilian transport sector is mainly marked by the alliance between the bourgeoisie, the government, and foreign companies; (ii) the availability of natural resources (sugarcane) and the pressure from the sugar sector were decisive for the evolution and innovation of the transport sector throughout history; (iii) dependence on imported fuel and foreign technology and the late industrialization and discovery of oil determined the evolution of the sector (bottleneck); (iv) the predominance of roads over other modes occurred with the construction of the public perception of the modernism of automobiles and was pressured by foreign investments in the formation of an automobile consumer market. As a result of the second paper, it was found that state market incentives are fundamental for the continuous development of alternative fuels such as natural gas to the already established liquid fuels in the country. In Rio de Janeiro, the advantages obtained through tax incentives to compressed natural gas and motor vehicle property taxes are crucial to decrease payback time and strengthen the price of natural gas. Otherwise, in the state of São Paulo, the lowest state value-added tax levied on hydrated ethanol and, consequently, the smallest price difference between fuels hinders the development of the compressed natural gas market. Finally, the results extracted from the two articles are discussed, summarizing the main lessons that can be learned and prospected in the Brazilian transport sector for a more sustainable and low carbon transition.